2004
DOI: 10.1021/ja0484707
|View full text |Cite
|
Sign up to set email alerts
|

pH-Sensitive Bipolar Ion-Permselective Ultrathin Films

Abstract: pH-Sensitive bipolar ion-permselective films of polyelectrolyte multilayers were prepared by layer-by-layer (LbL) assembly and photo-cross-linking of benzophenone-modified poly(acrylic acid) (PAA-BP) and poly(allylamine hydrochloride) (PAH-BP). The multilayer structure and ionizable group composition was finely tuned by changing the pH of the dipping solution. This structure and composition was in turn "preserved" by photo-cross-linking, forming highly stable membrane films. Since PAA-BP and PAH-BP are weak po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
188
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(195 citation statements)
references
References 42 publications
7
188
0
Order By: Relevance
“…[30] In general, BP is excited indirectly to the lowest triplet state (p-p*) by direct absorption into singlet state (p-p*) upon irradiation with UV light. [31] The BP ketyl radical and an on-chain polymer radical readily recombine to generate a new CÀC bond, [32] thereby resulting in cross-linking within the nanofibers (Figure 1 b). UV/Vis spectroscopy was used to monitor the cross-linking with BP.…”
mentioning
confidence: 99%
“…[30] In general, BP is excited indirectly to the lowest triplet state (p-p*) by direct absorption into singlet state (p-p*) upon irradiation with UV light. [31] The BP ketyl radical and an on-chain polymer radical readily recombine to generate a new CÀC bond, [32] thereby resulting in cross-linking within the nanofibers (Figure 1 b). UV/Vis spectroscopy was used to monitor the cross-linking with BP.…”
mentioning
confidence: 99%
“…These attributes are useful for controlled release and drug delivery [856,857]. For example, Rubner, Cohen, and coworkers introduced soft LbL films within the pores of a polymer support to prepare a pH-sensitive permeation valve (figure 100) [858].…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
“…Responsive LBL films deposited on the electrode surface are used as membrane-based sensors, where the membrane controls the transport of the redox species to a working electrode. [13,14] Weak PEs can be deposited with a high percentage of segments comprising loops and tails, by adsorbing under pH conditions of incomplete charge, and allowing for further large-scale reorganization and phase separation regulated by pH changes. It has been shown that such a reorganization causes phase separation in the LBL films, and results in the formation of a microporous membrane.…”
Section: Layer-by-layer Filmsmentioning
confidence: 99%